Timothy's Guide - Hanks, Billie; (1944-...) (China, 2009)
`Jesus expressed his personal concern about follow-up and spiritual nurture when he said 'Peter do you love Me? . Feed My lambs . Take care of My sheep . Feed My sheep (John 21:15-17, NIV). When you invest the time to follow up new believers and members, it is actually an evidence of your deep love for Christ. In the context of this book: a 'Discipler' is a Christian who is growing consistently in his relationship with Jesus Christ and is showing a younger believer how to mature in his faith and share his witness naturally. A 'Timothy' is a believer who is seeking to grow spiritually by spending time with a more experienced Christian. This equipping process is derived from the New Testament example of Paul who 'taught and trained' a growing young believer named Timothy.
Keywords: Discipling (Christianity)